KARAKTERISTIK MORFOMETRIK BIVALBIA DI KAWASAN PADAT INDUSTRI DI PESISIR LANGKAT SUMUTRA UTARA: KARAKTERISTIK MORFOMETRIK BIVALBIA DI KAWASAN PADAT INDUSTRI DI PESISIR LANGKAT SUMUTRA UTARA - Hariani, Indri; Mawardi, Abdul L.; Atmaja, T. Hadi Wibowo (JURNAL BIOSENSE, 2024)
The coastal area of ​​Pangkalan Susu is a place with diverse marine biota. Apart from being a spawning place and source of nutrition, coastal areas are also a source of food for various marine biota, including gastropods and bivalves Morphometry is the size or comparison of external body size between one part and another. This research was carried out in September 2023 on the coast of Pangkalan Susu, Langkat Regency. Sampling was carried out in plots. Bivalves are grouped into 3 length classes, namely small size (1.0 cm – 2.0 cm), medium size (2.1cm – 3.0 cm), large size (>3.1cm). Based on the collection of bivalve species at each location, 3 species of bivalves were obtained. The 3 species of bivalves obtained were Anadara granosa, Placuna placenta and Atrina pectinata. All bivalve species are large in size. Morphometrics of the three bivalve species showed that location 1 showed higher values ​​compared to location 1 in terms of length, width and weight. Key words: Bivalves; Morphometrics; Pangkalan Susu.